Germany : Financial Sector Assessment Program-Technical Note-Stress Testing, Interconnectedness, and Risk Analysis. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The financial sector weathered COVID relatively well on the back of high pre-crisis capital and liquidity buffers, strong public and private sector balance sheets, and unprecedented public and ECB support. Immediate risks to Germany's financial stability of Russia's invasion of Ukraine appear to be manageable due to the banks' limited direct exposures to Russia. However, risks associated with the economic fallout could impact some individual financial institutions, non-performing loans, and house prices. Real GDP growth was projected to regain momentum from mid-2022 onwards, but the war could hinder the recovery through supply constraints, higher-than-expected above-target inflation (with higher energy prices and supply constraints), a tightening of financial conditions, and shifts in investors' confidence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Germany